Best Practice Kemandirian Anak Usia Dini (Studi Implementasi 9 Pilar Karakter di Lembaga PAUD) - Sriyanti Sriyanti; Rizka Aisyah (ALSYS, 2026)
Independence is a crucial asset that children must develop from an early age to face the challenges of the digital era, yet studies that specifically evaluate the success of the 9 Pilar Karakter program of the Indonesian Heritage Foundation (IHF) in fostering independence among young children remain limited. This study aimed to examine the implementation and effectiveness of the 9 Pilar Karakter program in shaping independence in early childhood at BA Islamiyah Pesen, Kanor Subdistrict, Bojonegoro. A qualitative case study approach was employed with 14 children in Group A as the research subjects. Data were collected through observation, interviews, and documentation, and were analyzed using the interactive Miles and Huberman model, which includes data reduction, data display, and conclusion drawing. The findings show that implementation of the program through three main activities—knowing feeling, tell a story, and acting feeling—contributes to transforming children into more independent and self-confident individuals in their daily activities and learning context. These results affirm that the 9 Pilar Karakter program plays a strategic role in strengthening independence and socio-emotional character in early childhood. The implications of this study highlight the importance of optimizing the implementation of the 9 Pilar Karakter program as a foundation for children to navigate learning processes at subsequent educational levels as well as in everyday life.